(untitled) (SCIÉNDO INGENIUM, 2021)
The working climate as well as job satisfaction are of great importance for the development and growth of a company; the relationship between the two, can determine the good running of the organization or, if not, its failure. Therefore, the general objective of this study was to determine the relationship between the working climate and job satisfaction in employees in a company in the hydrocarbons sector of Chimbote in 2020. The type of research was descriptive – correlational, with a sample of 36 workers of the company. The survey technique used and as instruments the CL – SPC Labor Climate Scale and the SL – SPC Labor Satisfaction Scale. It concluded that there is a moderate positive correlation between the working climate and job satisfaction in the company under study.